PENYULUHAN KESEHATAN, PEMBAGIAN MASKER DAN PEMBAGIAN HAND SANITIZER DI LIMBANGAN - Gin Gin Sugih Permana; K Dewi Budiarti; Eti Suliyawati; Eva Daniati (Jurnal Pengabdian Masyarakat DEDIKASI, 2021)
The number of Covid-19 cases in West Java Province has shown a significant number in the past month. This is because West Java has become the center of very high community activity and mobility. Many people still don't understand how to prevent the spread of COVID-19, including the importance of using masks when leaving the house, the importance of personal hygiene, washing hands with soap, and physical distancing. The purpose of the Covid-19 counseling and training is to increase knowledge about preventing the transmission of Covid-19. Service activities are carried out in the form of education with leaflets and posters submitted by passing motorists and the surrounding community. Meanwhile, posters are installed in strategic places such as at the sub-district office, and in the RW/RT. The results obtained were an increase in knowledge after counseling by 26 people or an increase of 13%, citizens' knowledge about individuals susceptible to Covid-19 an increase of 17 people or 8.5%, an increase in knowledge about the signs of Covid19 symptoms by 43 people or an increase of 21, 5%, residents' knowledge about health procedures increased by 8 people or 4%, increased knowledge of residents about the types of Covid-19 masks by 37 people or 18.5%. The conclusions obtained from this activity are very useful and educate residents in preventing the spread of Covid-1